1989
DOI: 10.1080/1120009x.1989.11738911
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitors and Inactivators of Beta-Lactamase fromMycobacterium fortuitum

Abstract: The inhibiting or inactivating effects of some beta-lactam antibiotics on beta-lactamase from Mycobacterium fortuitum were studied. Among all substrates tested, clavulanic acid and sulbactam were the strongest competitive inhibitors of the enzyme although the latter was slightly hydrolyzed. Imipenem and cefoxitin scarcely inhibited the beta-lactamase yet expressed good activity against the microorganism in vitro, suggesting that the effectiveness of these drugs on M. fortuitum might be due to high permeation t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
6
0

Year Published

1990
1990
2001
2001

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 4 publications
3
6
0
Order By: Relevance
“…Addition of clavulanate partially decreased the MICs of amino-and ureidopenicillins, while tazobactam and sulbactam did not have any significant effect (Table 1). These results were consistent with those obtained for other N. asteroides isolates (9), for N. farcinica (11,20), and for Mycobacterium fortuitum (2,6). Disk susceptibility testing showed that the N. asteroides isolate JPL was also susceptible to aminoglycosides (except kanamycin), tetracycline, and sulfonamides and resistant to fluoroquinolones, macrolides, fosfomycin, and chloramphenicol.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Addition of clavulanate partially decreased the MICs of amino-and ureidopenicillins, while tazobactam and sulbactam did not have any significant effect (Table 1). These results were consistent with those obtained for other N. asteroides isolates (9), for N. farcinica (11,20), and for Mycobacterium fortuitum (2,6). Disk susceptibility testing showed that the N. asteroides isolate JPL was also susceptible to aminoglycosides (except kanamycin), tetracycline, and sulfonamides and resistant to fluoroquinolones, macrolides, fosfomycin, and chloramphenicol.…”
Section: Resultssupporting
confidence: 80%
“…As assessed by IC 50 s, the activity of inhibitors was weak, especially for sulbactam and tazobactam (Table 3). Similar results were obtained for ␤-lactamases extracted from N. asteroides, M. fortuitum, and N. farcinica (FAR-1) isolates (2,6,9,11). Thus, it may be hypothesized that ␤-lactamases of Nocardia spp.…”
Section: Resultssupporting
confidence: 72%
“…Purified P-lactamase of M. fortuitum hydrolyzes both penicillins and cephalosporins (1). Furthermore, this enzyme was inhibited by clavulanic acid and inactivated by isoxazolylpenicillins (10).…”
mentioning
confidence: 99%
“…Resistance to ␤-lactam antibiotics has been attributed to an interplay between ␤-lactamase activity and cell permeability as well as a low affinity to penicillin-binding proteins (12,15). ␤-Lactamase production by mycobacteria is likely to be an important factor in the expression of resistance to ␤-lactam antibiotics (11,12). Indeed, ␤-lactams in combination with either clavulanic acid or other ␤-lactamase inhibitors have in vitro activity against mycobacteria not observed with either agent alone (5,7,8,31).…”
mentioning
confidence: 99%